2012
DOI: 10.1007/s12031-012-9799-0
|View full text |Cite
|
Sign up to set email alerts
|

Orexin A Suppresses the Growth of Rat C6 Glioma Cells via a Caspase-Dependent Mechanism

Abstract: Orexin A and orexin B (also known as hypocretins) are closely related peptides synthesized by hypothalamic neurons. They orchestrate diverse central and peripheral processes by stimulation of two G-protein coupled receptors, OX1R and OX2R. Recent studies have demonstrated the ability of orexins to promote a robust apoptosis in different cancer cells in culture and a potent growth reduction of human colon tumors in mice xenografts. Here we report effects of orexins on survival of rat C6 glioma cells, an experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 39 publications
(52 reference statements)
1
37
0
2
Order By: Relevance
“…However, data on whether orexins regulate the growth of carcinoma cells are inconlcusive. Certain studies have found that orexins promote the growth of cancer cells (8,10), athough others have shown inhibitory effects (30,31). The different cell types used may be the reason for these conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…However, data on whether orexins regulate the growth of carcinoma cells are inconlcusive. Certain studies have found that orexins promote the growth of cancer cells (8,10), athough others have shown inhibitory effects (30,31). The different cell types used may be the reason for these conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…OX2R mRNA was expressed in rat pancreatic acinar tumor line AR42J (13). OX1R and OX2R were detected in rat C6 glioma cells (14). These cell lines exhibited decreased cell division and increased cell death upon orexin exposure.…”
Section: Discussionmentioning
confidence: 98%
“…Orexin A can induce apoptosis via OX2R in rat pancreatic tumor cells involving the caspase-3 and caspase-9 pathway (13). A study also found that orexin A induces p38/mitogen-activated protein kinase (MAPK)-and caspase-dependent cell death in rat C6 glioma cells (14).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…; 2013 [58] Relative standard curve Mean of peptidylprolylisomerase A (PpiA) and 18S rRNA SYBR Fang K.M. ; 2013 [59] Relative quantification (2 -deltadeltaCt) Cyclophilin A (CyPA) SYBR Wu Q.; 2013 [60] ND ND ND Biega nska K.; 2012 [61] Relative standard curve GAPDH SYBR Hattermann K.; 2012 [62] Relative quantification (2 -deltadeltaCt) GAPDH nd Lin Y.; 2012 [63] ND ACTB SYBR Liu J.; 2012 [64] Relative quantification (2 -deltadeltaCt) ACTB SYBR Zu H.; 2012 [65] Relative quantification (2 -deltadeltaCt) GAPDH ND Adach-Kilon A.; 2011 [66] Relative quantification (2 -deltadeltaCt) 18S rRNA SYBR Escartin C.; 2011 [67] Relative quantification (2 -deltadeltaCt) GAPDH SYBR Gatson J.W. ; 2011 [68] ND GAPDH SYBR Shu M.; 2011 [69] ND U6 snRNA SYBR Sugimoto T.; 2011 [70] Relative quantification (2 -deltadeltaCt) GAPDH SYBR Tsuchioka M.; 2011 [71] Relative quantification (2 -deltadeltaCt) GAPDH TaqMan Wang T.; 2011 [72] ND ACTB SYBR Yang L.; 2011 [73] ND ACTB ND Chen Y.Y.…”
Section: Systematic Reviewmentioning
confidence: 99%